Augmented reality smart glasses in the consumer sector: current status and challenges - Gebelhoff, Laura Simone (2022)
This paper addresses the current status and challenges of Augmented Reality Smart Glasses (ARSGs)in the consumer sector. It describes the penetration of the technology in the consumer market, and the prospects of the devices to dominate the market in the long run. While ARSGs are already widely used in industrial contexts, they have not yet been able to establish them selves in the consumer market. A look at the literature, a survey of potential consumers and interviews with experts in this field reveal that the device will not replace the smartphone in the next few years. There is no unanimous view amongst the interviewed experts regarding the breakthrough potential of ARSGs and the timing of its potential breakthrough. The conducted survey shows that the majority of respondents are aware of the technology, but only a minority have used it.